2019
DOI: 10.1177/0735633119854030
|View full text |Cite
|
Sign up to set email alerts
|

A Design Model for Using Virtual Reality in Behavioral Skills Training

Abstract: This study suggests a design model for developing virtual reality (VR)-based learning environments which can be used for basic behavioral skills training. VR-Based Fire Safety Training Environment (VR-FST) was designed considering the principles of the persuasive technology. Following the suggested model, VR-FST was setup by integrating head-mounted display and joysticks on the Second Life. Evaluations through participants’ perspectives indicated that the VR-FST environment designed through the proposed model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Several studies investigated the effectiveness of desktop VR on learning outcomes (Çakiroğlu & Gökoğlu, 2019; Passig et al., 2016). For example, Lee and Wong (2014) compared desktop VR with traditional lessons and found that college students displayed better performance on biology tests in VR simulation.…”
Section: Virtual Reality and Related Workmentioning
confidence: 99%
“…Several studies investigated the effectiveness of desktop VR on learning outcomes (Çakiroğlu & Gökoğlu, 2019; Passig et al., 2016). For example, Lee and Wong (2014) compared desktop VR with traditional lessons and found that college students displayed better performance on biology tests in VR simulation.…”
Section: Virtual Reality and Related Workmentioning
confidence: 99%
“…With the emergence of social sites like Facebook, WhatsApp, Instagram, and many others, 81% of Malaysians have become active SM users (Miller, 2021). We also identified persuasive design frameworks which will be giving positive behaviour effects towards various demographic groups, especially in global smartphone applications (Faisal, Nor and Abdullah, 2019), virtual reality (Çakiroğlu and Gökoğlu, 2019), and social media engagement (Muhamad & Shahrom, 2020). The vast development of social activities in the ICT platform allows PT to become more dominant as a social influencer for positive behaviour change.…”
Section: Social Media As Persuasive Technologymentioning
confidence: 99%
“…IVE-based instructions have the potential to facilitate education and transferring skills to a wide range of students with diverse backgrounds (Merchant, 2012). Limited work to date has focused on the use of IVEs in educating children about fire safety (Ahmad et al, 2019; Çakiroğlu & Gökoğlu, 2019; Ericson, 2007; Smith & Ericson, 2009), and there is a need to further explore the potential of IVEs in bushfire education programmes targeting children.…”
Section: Introductionmentioning
confidence: 99%